Effects of squat training on energy expenditure, oxygen consumption, and heart rate in young healthy adults - Indya del-Cuerpo; Pedro Delgado-Floody; Daniel Jerez-Mayorga; Felipe Caamaño-Navarrete; Mauricio Aliquintui-Flores; Luis Javier Chirosa-Ríos (Scientific Reports)
Abstract The main purpose of this study was to assess the changes in energy expenditure (EE), oxygen volume (VO2), heart rate (HR), and velocity (V) measurements obtained during three sets of each of two squat training protocols in a group of healthy young adults. Twenty-nine students of Sports Sciences volunteered to participate in this study. They attended the laboratory on four different days and performed four sessions: two of 3 sets of 12 repetitions at 75% 1 repetition maximum (RM) and two of 3 sets of 30 repetitions at 50% 1RM while EE, VO2, HR and V was evaluated. The major outcomes of this study indicated that EE, VO2, and HR tended to decrease in both protocols as the sets were performed. Despite this, assessing different strength levels and metabolic variables helps to explain the observed variations in physiological responses. Furthermore, these findings have important implications for the design of effective and personalized strength training programs.